OP76 Evaluating the health impacts of restrictions to income support for lone parents: a natural experiment study using understanding society. (2nd September 2017) - Katikireddi, SV; Molaodi, O; Gibson, M; Dundas, R; Craig, P
Abstract : Background: Lone parents experience poorer health and socioeconomic disadvantage compared to coupled parents. The UK Government has restricted access to Income Support, the primary income replacement benefit for lone parents. Under Lone Parent Obligations (LPO), lone parents are transferred from Income Support to Jobseeker's Allowance once their youngest child reaches an age threshold (which has been reduced incrementally), and they must prove they are actively seeking work or face sanctions. We investigated the effects of introducing LPO on the health of lone mothers in the UK. Methods: We analysed 2009–2013 data from Understanding Society, a panel study representative of the UK general population. Our primary outcome was the mental health component of SF-12, with the physical health component and self-rated health assessed as secondary outcomes. We identified two intervention groups: lone parents newly exposed following the cut-off change from seven to five years and from ten to seven years. Each of these intervention groups were compared to two control groups: remaining unexposed (since the youngest child was below the age cut-off), and already exposed (since the youngest child was older than the existing age cut-off). We estimated a pooled LPO effect to increase precision. We conducted a difference-in-difference analysis using linear regression to estimate the 'intention to treat' causal effect, adjusting for maternal age, number of children and maternal education. Multiple imputation was used to address item missingness. Results: Our primary analysis included a total of 2257 participants. Mental health of lone parents consistently declined in intervention groups compared to control groups, whereas physical health and self-rated health showed little change. For lone parents with children aged 5–7 years who were newly exposed, the mental health score of SF-12 changed by −1.39 (95%CI −4.08, 1.29) compared to those unexposed and −2.29 (95%CI −4.57, 0.00) compared to those remaining exposed. Equivalent figures for the cut-off change from 10–7 years were −2.45 (95%CI −5.48, 0.57) and −1.28 (95%CI −4.00, 1.45), while for the pooled effect were −2.13 (95%CI −4.17, −0.10) and −2.21 (95%CI −4.13, −0.30). A complete case analysis and inclusion of males within the analytical sample led to similar results. Discussion: Increasing conditionality attached to the receipt of welfare benefits adversely impacted mental health of lone mothers but had no short-term impacts on physical health. Our study had limited statistical power and was only able to investigate short-term effects, but the pattern of findings was consistent across comparison groups. Planned extensions to LPO should be reconsidered.